2021
DOI: 10.1088/1748-3190/abb86d
|View full text |Cite
|
Sign up to set email alerts
|

Tunabot Flex: a tuna-inspired robot with body flexibility improves high-performance swimming

Abstract: Tunas are flexible, high-performance open ocean swimmers that operate at high frequencies to achieve high swimming speeds. Most fish-like robotic systems operate at low frequencies (≤3 Hz) resulting in low swim speeds (≤1.5 body lengths per second), and the cost of transport (COT) is often one to four orders of magnitude higher than that of tunas. Furthermore, the impact of body flexibility on high-performance fish swimming remains unknown. Here we design and test a research platform based on yellowfin tuna (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 118 publications
0
68
0
Order By: Relevance
“…Peak power measurements are indicated by mechanical power peak P M , initial electrical power peak P (1) E (maximum electrical power value at first spike during acceleration), secondary electrical power peak P (2) E (maximum electrical power value of the oscillating power signal after initial spike in power), and t peak denotes the time to reach the initial electrical power peak. of the four body joints [16]. Furthermore, we found that the minimum body amplitude of (4:39 + 0:48) 10 À3 BL (mean ± s.d.)…”
Section: Results (A) Acceleration Performance and Body Kinematicsmentioning
confidence: 65%
See 4 more Smart Citations
“…Peak power measurements are indicated by mechanical power peak P M , initial electrical power peak P (1) E (maximum electrical power value at first spike during acceleration), secondary electrical power peak P (2) E (maximum electrical power value of the oscillating power signal after initial spike in power), and t peak denotes the time to reach the initial electrical power peak. of the four body joints [16]. Furthermore, we found that the minimum body amplitude of (4:39 + 0:48) 10 À3 BL (mean ± s.d.)…”
Section: Results (A) Acceleration Performance and Body Kinematicsmentioning
confidence: 65%
“…Tunabot Flex improved the mechanical and bioinspired designs of its predecessor, including variable body flexibility, while using the same external dimensions and motor. Added body flexibility was accomplished using a design that also enabled the generation of constant tail beat amplitudes at all tested frequencies, and the addition of body segments greatly increased swimming performance [16]. This body segment design involves small gaps between segments that open and close during swimming (figure 1), but visualization of flow in these regions indicated that water rapidly moved both in and out and did not reduce swimming performance.…”
Section: Methods (A) Tuna-like Robotmentioning
confidence: 99%
See 3 more Smart Citations